Prevalence and Risk Factors for Bacterial Vaginosis and Other Vulvovaginitis in a Population of Sexually Active Adolescents from Salvador, Bahia, Brazil. (22nd October 2012) - Moreira Mascarenhas, Rita Elizabeth; Sacramento Cunha Machado, Márcia; Borges da Costa e Silva, Bruno Fernando; Fernandes Weyll Pimentel, Rodrigo; Teixeira Ferreira, Tatiana; Silva Leoni, Fernanda Maria; Grassi, Maria Fernanda Rios
Abstract : Bacterial vaginosis, trichomoniasis, and genital candidiasis are considered the main etiologies of vulvovaginitis. Few studies estimate the prevalence of vulvovaginitis among adolescents, especially in Brazil. This study aimed to determine the prevalence and main risk factors associated with bacterial vaginosis and genital infection by C. albicans and Trichomonas vaginalis among a group of adolescents from Salvador, Bahia, Brazil. One hundred sexually active adolescents followed at an adolescent gynecology clinic were included. Endocervical and vaginal samples were obtained during gynecological examination. Nugent criteria were applied for the diagnosis of bacterial vaginosis. For Candida albicans and Trichomonas vaginalis detection, culture in Sabouraud agar plates and Papanicolaou cytology were used, respectively. The mean age of participants was 16.6 ± 1.6 years. The prevalence of bacterial vaginosis was 20% (95% CI 12–28) and of genital infection by Candida was 22% (95% CI 14–30). Vaginal cytology detected Trichomonas vaginalis in one patient. Alcohol, tobacco, and illegal drug use (P = 0.02 ) and multiple lifetime partners were statistically related to bacterial vaginosis (P = 0.01 ). The prevalence of bacterial vaginosis and genital candidiasis was similar to other studies carried out among adolescents worldwide.